2022
DOI: 10.3389/fphys.2022.847172
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Ratio of Soluble Fas/FasL Predicts Onset of Pulmonary Hypertension in Elder Patients Undergoing Maintenance Hemodialysis: A Prospective Cohort Study

Abstract: BackgroundPulmonary hypertension (PH) is one of the most common complications associated with end-stage renal disease (ESRD). Though numerous risk factors have been founded, other risk factors remain unidentified, particularly in patients undergoing maintenance hemodialysis with elder age. Soluble Fas (sFas) and its ligand FasL (sFasL) have been reported in chronic renal disease patients; however, they have not been identified in the PH patients of elder hemodialysis patients. We aimed to determine the roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Few of the existing articles have used either ‘multivariable logistic regression analysis’ or ‘propensity score matching’. It is expected that future studies will make greater use of these two methods to ensure that intergroup comparability and assessed relationships are not affected by other confounding factors ( Ding et al, 2022 ; Feng & Ren, 2020 ; Gao et al, 2021 ; He et al, 2015 ; Lv et al, 2019 ; Shen et al, 2021 ; Wang et al, 2014a , 2014b ; Yang & Bao, 2012 ; Yang & Bao, 2014 ; Zhang et al, 2020 ) (all the included articles are shown in 44–54 in the references).…”
Section: Discussionmentioning
confidence: 99%
“…Few of the existing articles have used either ‘multivariable logistic regression analysis’ or ‘propensity score matching’. It is expected that future studies will make greater use of these two methods to ensure that intergroup comparability and assessed relationships are not affected by other confounding factors ( Ding et al, 2022 ; Feng & Ren, 2020 ; Gao et al, 2021 ; He et al, 2015 ; Lv et al, 2019 ; Shen et al, 2021 ; Wang et al, 2014a , 2014b ; Yang & Bao, 2012 ; Yang & Bao, 2014 ; Zhang et al, 2020 ) (all the included articles are shown in 44–54 in the references).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, approximately 44% of HD patients suffer from HF [23]. A decline in left heart function can predict the occurrence of PH [6], which leads to category 2 PH [13]. Taken together, fluid volume can affect PCWP and left heart function, subsequently conducting the TRV of the right heart.…”
Section: Discussionmentioning
confidence: 99%
“…Among hemodialysis (HD) patients, the prevalence of PH ranges from 12.6% to 47% in different countries [2][3][4][5]. In Chinese individuals, the prevalence ranges from 34.6% to 39.1% [6,7]. PH is an important predictor of morbidity and mortality in patients with HD.…”
Section: Introductionmentioning
confidence: 99%